2012
DOI: 10.1007/s10661-012-2616-y
|View full text |Cite
|
Sign up to set email alerts
|

The source of DDT and its metabolites contamination in Turkish agricultural soils

Abstract: The concentration and impact of 1,1,1-trichloro-2,2-bis(4-chlorophenyl)-ethane (DDT) and its metabolites (DDE: 1,1-dichloro-2,2-bis(4-chlorophenyl)ethylene) on the environment was expected to decrease after its ban in the mid-1980s. Unfortunately, DDT contamination via its presence as an impurity in dicofol (2,2,2-trichloro-1,1-bis(4-chlorophenyl)ethanol) has led to a new source of contamination. This is particularly true especially in cotton production in Söke Plain, Turkey, where difocol-based pesticides are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…DDT and its degradation products were detected in soil samples collected from the Soke region of Aydin, Turkey [26]. The crop-specific models result showed that DDT and its degradation products primarily accumulate in the root, potato tuber, leafy vegetables with soil and cereals compared to leaves fruits, and water.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…DDT and its degradation products were detected in soil samples collected from the Soke region of Aydin, Turkey [26]. The crop-specific models result showed that DDT and its degradation products primarily accumulate in the root, potato tuber, leafy vegetables with soil and cereals compared to leaves fruits, and water.…”
Section: Resultsmentioning
confidence: 98%
“…0-30 cm, 30-60 cm, and 60-90 cm. The study results indicated that p,p′-DDT, p,p′-DDE, and o,p′-DDE levels were varied from 0.17-1.92 µg kg −1 , 0.003-0.24 µg kg −1 , and 0.018-0.48 µg kg −1 in different soil layers [26]. Sum values of the levels for p,p′-DDT, p,p′-DDE, and o,p′-DDE were used in crop-specific model which created by Legind and Trapp [10] to estimate plant uptake of p,p′-DDT, p,p′-DDE, and o,p′-DDE and their possible levels.…”
Section: Input Datamentioning
confidence: 90%
See 3 more Smart Citations